Modeling the Evolution of a Freshwater Lens under Highly Dynamic Conditions on a Currently Developing Barrier Island - Tobias Holt; Janek Greskowiak; Stephan L. Seibert; Gudrun Massmann (Geofluids)
The drinking water supply on barrier islands largely depends on freshwater lenses, which are also highly relevant for island ecosystems. The freshwater lens presented in this study is currently developing (since the 1970s) below the very young eastern part of the North Sea barrier island Spiekeroog, the so-called “Ostplate.” Due to the absence of coastal protection measures, formation, shape, and extent of the freshwater lens below the Ostplate are unaffected by human activities but exposed to dynamic changes, e.g., geomorphological variations and storm tides. The main aim of this paper was to reconstruct the evolution of the freshwater lens over several decades in order to explain the present-day groundwater salinity distribution. In addition, the study assessed the impact of geomorphological variations and storm tides on the freshwater lens formation. Detailed field observations were combined with a transient 2-D density-dependent modeling approach. Both field observations and simulations show an asymmetric freshwater lens after ~42 years of formation, whereby the horizontal extent is limited by the elevated dune area. The simulations indicate that the young freshwater lens has nearly reached quasi-steady-state conditions mainly due to the continuous mixing with seawater infiltrating during storm tides, which inhibits further growth of the freshwater lens on the narrow island. The findings further show that (i) a neglection of storm tides results in a significant overestimation of the freshwater lens extent, and (ii) the modeled present groundwater salinity distribution and shape of the freshwater lens are predominantly determined by the position and extent of the elevated dune area at the past ~20 years. Hence, annual storm tides have to be directly implemented into numerical models to explain the groundwater salinity distribution and the extent of young freshwater lenses located in highly dynamic tidal environments.